2018
DOI: 10.1111/obr.12690
|View full text |Cite
|
Sign up to set email alerts
|

A cumulative meta‐analysis of the effects of individual physical activity interventions targeting healthy adults

Abstract: SummaryDespite a large and increasing evidence base on physical activity interventions, the high rates of physical inactivity and associated chronic diseases are continuing to increase globally. The purpose of this cumulative meta‐analysis was to investigate the evolution of randomized controlled trial evidence of individual‐level physical activity interventions to asses if new trials are contributing novel evidence to the field. Through a two‐staged search process, primary studies examining the effects of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 29 publications
0
23
0
1
Order By: Relevance
“…Our study showed no long-term changes in HLC participants’ PA levels. Although previous controlled clinical trials of PA interventions have shown positive effects among healthy populations [ 56 ] and groups with specific conditions [ 57 , 58 ], implementing such programs into a real-life setting is challenging, and the knowledge about effective interventions within primary care to achieve long-term effects among high-risk groups remains unclear [ 12 , 59 ]. The HLC population comprises a heterogeneous group with multiple health challenges [ 22 , 50 , 51 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed no long-term changes in HLC participants’ PA levels. Although previous controlled clinical trials of PA interventions have shown positive effects among healthy populations [ 56 ] and groups with specific conditions [ 57 , 58 ], implementing such programs into a real-life setting is challenging, and the knowledge about effective interventions within primary care to achieve long-term effects among high-risk groups remains unclear [ 12 , 59 ]. The HLC population comprises a heterogeneous group with multiple health challenges [ 22 , 50 , 51 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results highlight the potential to prevent CVD among older adults by replacing sedentary behaviour with walking, and among both adults and older adults by replacing sedentary behaviour with HIPA. Since individual behavioural change is challenging [61], a systems-based approach to increase physical activity is increasingly recognised [7,62]. This can involve multi-disciplinary collaborations between researchers and stakeholders where research is designed and solutions created across different societal 'systems' (e.g., environment, policy-making and regulation, work-places, communities, health-care, education, etc.)…”
Section: Perspectivesmentioning
confidence: 99%
“…Several attempts have been made to implement different types of exercise prescription models in different countries with varying results,7 and there is evidence that PA interventions may be useful for increasing PA in healthy adults 8…”
Section: Introductionmentioning
confidence: 99%